2019
DOI: 10.1111/gcb.14552
|View full text |Cite
|
Sign up to set email alerts
|

Four decades of functional community change reveals gradual trends and low interlinkage across trophic groups in a large marine ecosystem

Abstract: The rate at which biological diversity is altered on both land and in the sea, makes temporal community development a critical and fundamental part of understanding global change. With advancements in trait‐based approaches, the focus on the impact of temporal change has shifted towards its potential effects on the functioning of the ecosystems. Our mechanistic understanding of and ability to predict community change is still impeded by the lack of knowledge in long‐term functional dynamics that span several t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
28
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 79 publications
(119 reference statements)
2
28
1
Order By: Relevance
“…In contrast, the seabed in the permanently anoxic basins of the central Baltic Sea is often referred to as a 'dead zone' due to the mass mortality and disappearance of benthos (Diaz andRosenberg 2008, Gogina et al 2016). In our analysis, benthos and fish communities in this area seem to follow different dynamics, with fish community variability contributing to the first axis of variation, whereas the benthos community contributes to the second axis, pointing towards a potential decoupling between the groups, as has been shown in coastal areas (Törnroos et al 2019). The biological interactions between benthos and pelagic consumers are indeed expected to decrease under hypoxia or anoxia, impacting benthic-pelagic coupling (Griffiths et al 2017).…”
supporting
confidence: 50%
See 2 more Smart Citations
“…In contrast, the seabed in the permanently anoxic basins of the central Baltic Sea is often referred to as a 'dead zone' due to the mass mortality and disappearance of benthos (Diaz andRosenberg 2008, Gogina et al 2016). In our analysis, benthos and fish communities in this area seem to follow different dynamics, with fish community variability contributing to the first axis of variation, whereas the benthos community contributes to the second axis, pointing towards a potential decoupling between the groups, as has been shown in coastal areas (Törnroos et al 2019). The biological interactions between benthos and pelagic consumers are indeed expected to decrease under hypoxia or anoxia, impacting benthic-pelagic coupling (Griffiths et al 2017).…”
supporting
confidence: 50%
“…6). Previous work on multi-trophic communities found divergent directional trends across taxa when looking at aggregated trait diversity metrics, such as turnover, divergence or evenness (Concepción et al 2017, Magurran et al 2018, Törnroos et al 2019). Previous work on multi-trophic communities found divergent directional trends across taxa when looking at aggregated trait diversity metrics, such as turnover, divergence or evenness (Concepción et al 2017, Magurran et al 2018, Törnroos et al 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Few studies indicated distinct spatial [53] and long-term variability [14, 54] in taxonomic and trait-based community structures, which were related to anthropogenic and natural factors such as sediment properties, fishing pressure, depth, and temperature [14]. In the Baltic Sea, Törnroos et al [55] found distinct long-term trends of two key organismal groups, fish and zoobenthos, over a 40 year period. A similar timing of changes in fish and macrofauna were found, amongst others in the early 1990s and the late 2000s [56].…”
Section: Introductionmentioning
confidence: 99%
“…In support for our first hypothesis, the eutrophication process affects the zoobenthic assemblage composition: even if nutrient concentrations were significant explanatory variables, it was best manifested through the indirect secondary effects of eutrophication, i.e., changes (reductions) in oxygen concentration as a consequence of increased sedimentation of pelagic primary production and thus increased oxygen demand (Griffiths et al, 2017). As the sampling was temporally infrequent (annual), and the water chemical variables were not always measured during the same day as zoobenthic samples, it cannot be ruled out that higher levels of correlation and direct influence of the chosen environmental factors would have been seen closer to the zoobenthos sampling time (e.g., Weigel et al, 2015), although time-series studies with once-per-year sampling have proven to be fruitful before in this marine to brackish-water region (Rousi et al, 2013;Törnroos et al, 2019).…”
Section: Discussionmentioning
confidence: 99%